SEASONAL VARIATION IN AI AND PREGNANCY RATE IN BUFFALO AND IMPROVING THEIR FERTILITY STATUS FOLLOWING APPLICATION OF FTAI DURING NON-BREEDING SEASON - GHUMAN, S P S; DHAMI, D S (The Indian Journal of Animal Reproduction, 2022)
SEASONAL VARIATION IN AI AND PREGNANCY RATE IN BUFFALO AND IMPROVING THEIR FERTILITY STATUS FOLLOWING APPLICATION OF FTAI DURING NON-BREEDING SEASON
Keywords: Buffalo; Conception; Estradiol; FTAI; Season